Digital Parenting Interventions for Fathers of Infants From Conception to the Age of 12 Months: Systematic Review of Mixed Methods Studies - Elisabeth Bailin Xie; James Wonkyu Jung; Jasleen Kaur; Karen M Benzies; Lianne Tomfohr-Madsen; Elizabeth Keys (JMIR Publications, 2023)
BackgroundDigital interventions help address barriers to traditional health care services. Fathers play an important parenting role in their families, and their involvement is beneficial for family well-being. Although digital interventions are a promising avenue to facilitate father involvement during the perinatal period, most are oriented toward maternal needs and do not address the unique needs of fathers. ObjectiveThis systematic review describes the digital interventions that exist or are currently being developed for fathers of infants from conception to 12 months postpartum. MethodsA systematic search of the MEDLINE, PsycINFO, Cochrane Central Register of Controlled Trials, Embase (using Ovid), and CINAHL (using EBSCO) databases was conducted to identify articles from database inception to June 2022, of which 39 met the inclusion criteria. Articles were included if they were peer-reviewed and described a digital intervention that targeted fathers of fetuses or infants aged ≤12 months. Systematic reviews, meta-analyses, and opinion pieces were excluded. Data from these studies were extracted and themed using a narrative synthesis approach. Quality appraisal of the articles was conducted using the Mixed Methods Appraisal Tool. ResultsA total of 2816 articles were retrieved, of which 39 (1.38%) met the inclusion criteria for eligibility after removing duplicates and screening. Eligible articles included 29 different interventions across 13 countries. Most articles (22/29, 76%) described interventions that were exclusively digital. There were a variety of digital modalities, but interventions were most commonly designed to be delivered via a website or web-based portal (14/29, 48%). Just over half (21/39, 54%) of the articles described interventions designed to be delivered from pregnancy through the postpartum period. Only 26% (10/39) of the studies targeted fathers exclusively. A wide range of outcomes were included, with 54% (21/39) of the studies including a primary outcome related to intervention feasibility. Qualitative and mixed methods studies reported generally positive experiences with digital interventions and qualitative themes of the importance of providing support to partners, improving parenting confidence, and normalization of stress were identified. Of the 18 studies primarily examining efficacy outcomes, 13 (72%) reported a statistically significant intervention effect. The studies exhibited a moderate quality level overall. ConclusionsNew and expecting fathers use digital technologies, which could be used to help address father-specific barriers to traditional health care services. However, in contrast to the current state of digital interventions for mothers, father-focused interventions lack evaluation and evidence. Among the existing studies on digital interventions for fathers, there seem to be mixed findings regarding their feasibility, acceptability, and efficacy. There is a need for more development and standardized evaluation of interventions that target father-identified priorities. This review was limited by not assessing equity-oriented outcomes (eg, race and socioeconomic status), which should also be considered in future intervention development.